Violence Prevention Policy in Higher Education: Comparative Study of Permendikbudristek Number 30 of 2021 and Number 55 of 2024 - Nur Angraini, Peggy Dian Septi (LEGAL BRIEF, 2025)
Education develops human resources. Higher education is prone to sexual violence. The response to sexual violence in higher education, the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) issued Permendikbudristek Number 30 of 2021 to prevent and handle sexual violence and Permendikbudristek Number 55 of 2024 to prevent and handle violence. Normative legal research qualitative descriptive analysis of secondary data sources. Permendik-Budristek Number 30 of 2021 is limited to sexual violence, recruitment of long-term task forces with unclear positions, handling of violence in the implementation of Tridharma, unclear handling of cases not related to the implementation of Tridharma, and the budget is not yet detailed. Permendik-Budristek Number 55 of 2024 physical violence, mental violence, bullying, sexual violence, differences and intolerance, and policies related to violence. The recruitment of task forces clearly takes into account the lack of human resources, adding to the implementation of the Tridharma, violence mechanisms that are not related to the implementation of the Tridharma to other mechanisms, and budgets implemented by Universities. Universities must be safe from violence, citizens have the right to be free from differences, oppression, and violence. Maintaining the value of the University, the maximum potential for happiness is formed, comfortable and safe for learning work. If there is violence, the University must not allow it to be imposed sanctions so as not to increase violations